Researching Performance of the Dubins Vehicle’s Hybrid Model with a Single Separation of the Control Objects - Bortakovskii, A. S.; Uryupin, I. V. (Journal of computer & systems sciences international, 2024)
The problem of the performance of a hybrid system in which the number of control objects changes during its operation is considered. Movement is started by one control object (carrier). At some point in time, several moving objects are separated from it and sent to specified terminal states (targets). The carrier is represented by a hybrid model of the Dubins vehicle, allowing trajectories of unlimited curvature. The movement of separated objects is rectilinear with limited speeds and accelerations. The problem of minimizing the time to achieve all targets is solved.